Fertilization alternatives using biostimulants and biofertilizers for potato cultivation (solanum tuberosum l.) in Montúfar – Carchi - Mora Quilismal, Segundo Ramiro; Flores Ayala, Steven; Chulde Minda, John; Puetate Mejía, Luis; Revelo Ruales, Vinicio (SATHIRI, 2021)
The research evaluated different alternatives of fertilization in potato (Solanum tuberosum L.) Superchola variety, using local production Biol, phosphorus solubilizer microorganisms and seaweed extracts. The experiment was carried out in open field conditions, using a Completely Random Block Design (DBCA), with 7 treatments and 4 repetitions, total 28 experimental units. Each unit contained 30 plants of which six were taken for a total of 168 plants as a sample. The variables assessed were: Emergency percentage, plant height, stem diameter, number of stems, yield per plant and cost-benefit ratio (C/B). The evaluated alternatives were conbinaron with amounts of Fertilization Phosphate (NPK) used in the region, were fractionated to compare the production and costs of cultivation, important in the area. The T2 (100% NPK + Fosfotic) was the treatment that increased yield, with a weight of tubers of 2.29 Kg/plant and a quantity of first category of 12.88 tubers/plant. The positive results obtained, confirm the use of alternatives of biofertilization, thanks to the appropriate interaction of NPK and BSF that improve the consumption of nutrients present and conditioned in the soil, reforming the costs of production and Maintaining an appropriate return for the farmer in the area. According To The economic analysis, the treatment that obtained the best profitability was T2, with a cost/benefit (C/B) of-0.11 USD increasing the yield, which compared with the control T1 (100% NPK) which has a utility of-0.20 USD, is better.
Keywords: Superchola; Biol; phosphorus solubilizing microorganisms; seaweed extracts